Unconventional oil and gas resources handbook : evaluation and development - Ma, Y. Zee; Holditch, Stephen A. (Waltham, MA : Gulf Professional Publishing in an imprint of Elsevier, 2015)
Annotation 'Unconventional Oil and Gas Resources Handbook' is a must-have, helpful handbook that brings a wealth of background information to the engineer and geologist alike. Bridging between subsurface and production, the handbook extends your reservoir's potential by providing multiple layers of methods to lead you to a better defined reservoir. Better reservoir knowledge and more sophisticated technology are making unconventional resources economically possible, but for young and even experienced engineers, this kind of reservoir is new and complex, making identification and characterization difficult and confusing.
2.1.4 monte carlo probabilistic approach2.2 methodology; 2.3 global unconventional gas original gas-in-place assessment; 2.3.1 cbm ogip; 2.3.2 tight gas ogip; 2.3.3 shale gas original gas-in-place; 2.4 technically recoverable resources recovery factor; 2.4.1 coal bed methane recovery factors; 2.4.2 tight gas recovery factors; 2.4.3 shale gas recovery factors; 2.5 global recoverable unconventional gas resource evaluation; 2.5.1 coal bed methane technically recoverable resources; 2.5.2 tight gas technically recoverable resources; 2.5.3 shale gas trr; 2.6 discussion; 2.7 conclusion; nomenclature
Includes index.
REFERENCES3 - GEOCHEMISTRY APPLIED TO EVALUATION OF UNCONVENTIONAL RESOURCES; 3.1 INTRODUCTION; 3.1.1 SUBSURFACE EVOLUTION OF ORGANIC MATTER; 3.1.2 CONVENTIONAL VERSUS UNCONVENTIONAL RESOURCES; 3.1.3 EMPIRICAL MEASURES OF SWEET SPOTS; 3.2 DISCUSSION; 3.2.1 ORGANIC GEOCHEMICAL AND PETROPHYSICAL CHARACTERIZATION; 3.2.1.1 Rock-Eval Pyrolysis; 3.2.1.2 Total Organic Carbon; 3.2.1.3 Geochemical Methods for TOC; 3.2.1.4 Indirect Wireline TOC; 3.2.1.5 Direct Wireline TOC; 3.2.2 ORGANIC GEOCHEMICAL LOGS AND ANCILLARY TOOLS; 3.2.2.1 Van Krevelen Diagrams; 3.2.2.2 TOC versus S2 Plots
Online resource; title from PDF title page (ScienceDirect, viewed October 21, 2015).
Elsevier
Keywords: Petroleum engineering -- Handbooks, manuals, etc; Petroleum -- Prospecting -- Handbooks, manuals, etc; TECHNOLOGY & ENGINEERING / Power Resources / General; Petroleum engineering; Petroleum -- Prospecting; Electronic books; Handbooks and manuals; Electronic books